2010
DOI: 10.1016/j.chiabu.2010.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Associations between childhood adversity and depression, substance abuse and HIV and HSV2 incident infections in rural South African youth

Abstract: Objectives-to describe prevalence of childhood experiences of adversity in rural South African youth and their associations with health outcomes.Methods-we analysed questionnaires and blood specimens collected during a baseline survey for a cluster randomized controlled trial of behavioral intervention, and also tested blood HIV and herpes simplex type 2 virus at 12 and 24 month follow up; 1,367 male and 1,415 female volunteers were recruited from 70 rural villages. CI 0.99, 4.72, p=0.05), and incident HSV2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
223
4
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(245 citation statements)
references
References 25 publications
15
223
4
3
Order By: Relevance
“…The distribution of physical and psychological abuses of the sample is summarized in Table 1. Similar to our results, the results of other studies have also shown a correlation between various types of violence and psychological distress, depression (12)(13)(14)(15), anxiety (16)(17)(18)(19)(20), and depression and anxiety (5,(21)(22)(23).…”
Section: Resultssupporting
confidence: 81%
“…The distribution of physical and psychological abuses of the sample is summarized in Table 1. Similar to our results, the results of other studies have also shown a correlation between various types of violence and psychological distress, depression (12)(13)(14)(15), anxiety (16)(17)(18)(19)(20), and depression and anxiety (5,(21)(22)(23).…”
Section: Resultssupporting
confidence: 81%
“…As well as biological mechanisms, socioeconomic and behavioural aspects are considered to be relevant for the demonstrated link between child maltreatment and health conditions in adulthood. The discussed pathways comprise altered health behaviour, encompassing a higher risk for substance abuse and risky sexual behaviour (Abajobir, Kisely, Williams, Strathearn, & Najman, 2017; Jewkes, Dunkle, Nduna, Jama, & Puren, 2010; Norman et al, 2012) and higher rates of smoking (Edwards, Anda, Gu, Dube, & Felitti, 2007; Taha, Galea, Hien, & Goodwin, 2014), as well as strikingly increased rates of mental health problems and suicide attempts (Lereya, Copeland, Costello, & Wolke, 2015; Norman et al, 2012; Winsper, Lereya, Zanarini, & Wolke, 2012). Hypothesized socioeconomic aspects comprise impaired social networks and relationships (Colman & Widom, 2004; Sperry & Widom, 2013), lower academic achievement (Fry et al, 2017; Tanaka, Georgiades, Boyle, & MacMillan, 2015) and lower socioeconomic status (Currie & Widom, 2010; Pinto Pereira, Li, & Power, 2017; Zielinski, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, the current study considered prevalence of all cancers overall, in childhood and adulthood, in a cross-sectional study with a population-based sample while Brown et al (2010) looked at incident lung cancer using a prospective study design [15]. Evidence suggests that ACEs have been associated with risky sexual behaviors, [17][18][19] sexually transmitted infections, [7,8,19] chronic diseases such as cancer, [15,16] obesity, [42] depression [7,8,12,13], and smoking [42,43]. Research has also shown that ACEs are associated with risk factors for chronic disease [15] such as chronic obstructive pulmonary disease [44], liver disease [4], and ischemic heart disease [14].…”
Section: Discussionmentioning
confidence: 99%
“…ACEs have been linked to substance abuse [7][8][9][10][11], depression [7,8,12,13], cardiovascular disease [7,14], diabetes [7], cancer [7,15,16], risky sexual behaviors [17][18][19], sexually transmitted infections [7,8,19] suicidality [7,8,13,17,18], and premature mortality in adulthood [17]. Researchers have suggested examining multiple ACEs allowing for a potential assessment of a graded relationship between these exposures and health outcomes [6].…”
Section: Introductionmentioning
confidence: 99%